2006
DOI: 10.2105/ajph.2005.065722
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities for Type 2 Diabetes Mellitus Screening Among Women With a History of Gestational Diabetes Mellitus

Abstract: These findings suggest that most women with gestational diabetes mellitus are not screened for type 2 DM after delivery. Opportunities for DM prevention and early treatment are being missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 14 publications
8
101
1
1
Order By: Relevance
“…20,[22][23] Yet even women with pregnancy complications often miss their postpartum visits. 22,[24][25][26][27][28] Low-income women-who have disproportionate prevalence of gestational diabetes and hypertensive disorders in pregnancy 4,[29][30] -have multiple barriers to outpatient follow-up in the postpartum period. 31 These barriers include lack of childcare, schedule demands, difficulty accessing care, and lack of understanding about the long-term health risks associated with pregnancy complications 31 and may increase women's reliance on emergency room (ER) settings.…”
Section: In 2008 Inmentioning
confidence: 99%
“…20,[22][23] Yet even women with pregnancy complications often miss their postpartum visits. 22,[24][25][26][27][28] Low-income women-who have disproportionate prevalence of gestational diabetes and hypertensive disorders in pregnancy 4,[29][30] -have multiple barriers to outpatient follow-up in the postpartum period. 31 These barriers include lack of childcare, schedule demands, difficulty accessing care, and lack of understanding about the long-term health risks associated with pregnancy complications 31 and may increase women's reliance on emergency room (ER) settings.…”
Section: In 2008 Inmentioning
confidence: 99%
“…For example, as the population becomes obese at earlier ages, women with GDM may have a history of more prolonged insulin resistance, rendering risk predictions based on age less accurate. Second, recommended postpartum screening after the index pregnancy needs to increase from its current suboptimal levels (34). Such screening may result in identification of preexisting diabetes; outcomes in subsequent pregnancies affected by frank diabetes may then be improved by preconception care as well as closer monitoring during the pregnancy (35).…”
Section: Other Risk Factorsmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28] However, in Australia, where there is a greater focus on postpartum screening, data indicate that levels are as high as 73%. 29 There is a paucity of data on long-term follow-up; a US study indicated that approximately 40% of females were not tested at all in a 5-year period postpartum.…”
mentioning
confidence: 99%